Seasonality and dynamics of schistosomiasis in the environment: usefulness of environmental DNA (eDNA) surveillance system at a community level for risk mapping schistosomiasis in Ekiran Village, Leyte, Philippines - Mark June Revolteado; Marcello Otake Sato; Joseph Valencia; Mario Jiz; Eleonor Cervantes; Ralph Aniceto; Marianette Inobaya; Darren Gray; Catherine A. Gordon; Pengfei Cai; Yasuhito Sako; Megumi Sato (mSphere)
ABSTRACT Schistosomiasis, primarily caused by Schistosoma japonicum (Sj) in Asia, remains a major health concern in the Philippines, affecting 12.4 million people and causing symptoms like fever, abdominal pain, and hepatosplenomegaly. Chronic disease leads to stunting in children, and reinfection persists despite efforts to reduce morbidity. Current strategies focused on mass drug administration (MDA) and sporadic snail surveys, leaving gaps in monitoring and mitigating schistosomiasis transmission in the environment. To address these issues, this study refined an environmental DNA (eDNA)-based qualitative real-time polymerase chain reaction assay by making it field-applicable and multiplex, to detect both the parasite S. japonicum and its intermediate snail host, Oncomelania hupensis quadrasi (Ohq), using water samples. We surveyed the 30 sentinel sites quarterly—from July 2023 to March 2024—in Ekiran Village, Alangalang, Leyte, Philippines. Collectively, the eDNA of O.h. quadrasi was detected in 18 sites and that of S. japonicum eDNA was detected in 16 sites, while direct snail observation confirmed the presence in only five sites, with infected snails found in only one site. Consequently, the assay described temporal variation of Ohq and Sj, revealing the dynamics of Ohq colonies and Sj in Ekiran’s water sources. The eDNA confirmed the focality of Ohq and showed the erratic presence of Sj. Interestingly, both target species’ eDNA was observed more during the rainy season (December and March), which suggests a higher infection probability during this period. Integrating eDNA detection system with the existing control programs will enhance the identification of transmission hotspots, which may aid in reducing exposure risk for both humans and animals in the endemic areas.IMPORTANCEThis study aimed to fill the gaps in monitoring and mitigating schistosomiasis transmission in the environment. This field-applicable environmental DNA (eDNA)-based qualitative real-time polymerase chain reaction (qPCR) detection system focused on effectively detecting Schistosoma japonicum and its snail intermediate host, Oncomelania hupensis quadrasi, at the community level, moving from the traditional detection methods that are labor-intensive, less sensitive, and exposing surveyors to potential risk of infection. By introducing a field-applicable eDNA-based qPCR assay, this research provides a sensitive, non-invasive, and rapid molecular method for detecting S. japonicum and O.h. quadrasi in the environment. Additionally, the study not only provided insights in enhanced surveillance strategies but also contributed to a holistic eco-health approach by generating hazard maps for potential transmission and contamination sites, which could improve future control efforts and resource allocation for schistosomiasis elimination.